Calcium Sensing Receptor as a Novel Mediator of Adipose Tissue Dysfunction: Mechanisms and Potential Clinical Implications - Bravo-Sagua, Roberto; Mattar, Pamela; Díaz, Ximena; Lavandero, Sergio; Cifuentes, Mariana (Frontiers in Physiology, 2016)
Obesity is currently a serious worldwide public health problem, reaching pandemic levels. For decades, dietary and behavioral approaches have failed to prevent this disease from expanding, and health authorities are challenged by the elevated prevalence of co-morbid conditions. Understanding how obesity-associated diseases develop from a basic science approach is recognized as an urgent task to face this growing problem. White adipose tissue is an active endocrine organ, with a crucial influence on whole-body homeostasis. White adipose tissue dysfunction plays a key role linking obesity with its associated diseases such as type 2 diabetes mellitus, cardiovascular disease and some cancers. Among the regulators of white adipose tissue physiology, the calcium-sensing receptor has arisen as a potential mediator of white adipose tissue dysfunction. Expression of the receptor has been described in human preadipocytes, adipocytes, and the human adipose cell lines LS14 and SW872. The evidence suggests that calcium-sensing receptor activation in the visceral (i.e. unhealthy) white adipose tissue is associated with an increased proliferation of adipose progenitor cells and elevated adipocyte differentiation. In addition, exposure of adipose cells to calcium-sensing receptor activators in vitro elevates proinflammatory cytokine expression and secretion. An increased proinflammatory environment in white adipose tissue plays a key role in the development of white adipose tissue dysfunction that leads to peripheral organ fat deposition and insulin resistance, among other consequences. We propose that calcium-sensing receptor may be one relevant therapeutic target in the struggle to confront the health consequences of the current worldwide obesity pandemic.